A Proposal for Improving the Essence Standard by Using Terminology Unification - Zapata Jaramillo, Carlos Mario; Henao Roqueme, Antony (Ingeniería, 2021)
Context: SEMAT (Software Engineering Method and Theory) is promoting a software engineering theory with adequate terminology to improve the transference of methods and practices between teams. Terminologies should be uniform in order to eliminate ambiguity, improve communication among teams, and support new concepts. Method: The process of reaching uniformity is called terminology unification. In this paper we propose a method for improving the Essence standard based on terminology unification. This method comprises four stages: selection of base models and definitions for structuring terms, identification of terminology problems by comparing the base models and definitions, unification of terms among the base models and definitions, and measurement of the gap between the current standard terms and the proposed changes. Results: We propose a set of modifications to the Essence standard in constructs like: alpha state cards, relationships among alphas, and names of activity spaces. Conclusions: By solving such conflicts, we can define a common, unambiguous terminology for software engineering teams.